Economics of biofortification - Qaim, Matin; Stein, Alexander J.; Meenakshi, J. V. (Wiley, 2007)
Micronutrient malnutrition is a serious public health problem in many developing countries. Different interventions are currently used, but their overall coverage is relatively limited. Biofortification—that is, breeding staple food crops for higher micronutrient contents—is a new agriculture‐based approach, but relatively little is known about its ramifications. Here, the main factors influencing success are discussed and a methodology for economic impact assessment is presented. Ex ante studies from India and other countries suggest that biofortified crops can reduce the problem of micronutrient malnutrition in a cost‐effective way, when targeted to specific situations. Further research is needed to corroborate these findings and address certain issues still unresolved.